(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2026)
The integration of computational thinking in elementary education is essential to support students’ reasoning and problem-solving skills, particularly in science learning. However, limited access to computers in many elementary schools remains a barrier to the implementation of coding-based instruction. Unplugged coding offers a promising non-digital approach, yet teachers’ readiness has not been widely examined. This study aims to analyze elementary school teachers’ knowledge, perceptions, and readiness regarding the implementation of unplugged coding in science learning. An exploratory mixed-methods design was employed involving 18 public elementary school teachers in Jakarta. Quantitative data were collected through questionnaires and analyzed descriptively, while qualitative data were obtained through semi-structured interviews and analyzed thematically. The results indicate that teachers’ knowledge is at a moderate level, with limitations in core computational thinking concepts. Teachers hold positive perceptions; however, their readiness to implement unplugged coding remains moderate to low, particularly in lesson design, curriculum alignment, and assessment.